The industry perspective on marketability of palm oil biodiesel to domestic end users / Muhammad Ashraf Ahmad Husaini Zakwan - Ahmad Husaini Zakwan, Muhammad Ashraf (Faculty of Business and Management, 2009)
Petroleum-based fuels are limited reserves concentrated in certain regions of the world. Previously the price of crude oil increase double folded. In additional, these sources are in the verge of getting extinct. The scarcity of known petroleum reserves will make renewable energy resources more attractive. The best option among the available renewable energy is biodiesel. Hence, to produce biodiesel comes from various vegetable oil. Palm oil has become the best choice of oil for producing biodiesel due to it high yield per hectare and high extraction rate compare to other crops. Even though Malaysia is the major exporter and the largest producer of palm oil, recently, is still pending on implementing palm oil base biodiesel domestically. Thus, palm oil based biodiesel in Malaysia is utilized by exporting to the other part of the world, particularly in European countries. There were several issues that contribute to biodiesel industry for not implementing biodiesel domestically. The main input price for biodiesel is fluctuate, consequently its affect the final price for biodiesel that would be inconsistent. Malaysian government develop National Biofuel Policy (NBP) in 2005, however some of the policy were not been executed. In view of the fact that palm oil is the major input for biodiesel, it is also the main sources for edible products, as a result, there is a dispute between balancing palm oil biodiesel with the food requirement. Lastly, engine manufacturers are refused to extend engines warranties for biodiesel and thus affect the industry to promote biodiesel domestically.